Hubungan Tingkat Kebiasaan Merokok dengan Stadium Katarak Senilis di Poliklinik Katarak dan Bedah Refraktif (KBR) Rumah Sakit Mata Cicendo Bandung (Universitas Kristen Maranatha, 2020)
Cataract is the leading cause of blindness in the world, including Indonesia. Senile cataract is the most common type of cataract, caused by the aging process, and involving many factors such as genetic, ultraviolet radiation, dietary factors, dehydration, and smoking. Smoking is one of the causes involved in the maturity of cataract release due to the accumulation of the 3-hydroxykhynurine molecules and chromophores that have roles in changing the color of the lens. This research aimed to find the relationship between smoking levels and senile cataract severity. This is descriptive correlative research with a cross-sectional approach. The subjects were senile cataract patients with smoking habits at the cataract and refractive surgery clinic of Cicendo Eye Hospital Bandung, Indonesia. We recruited 337 patients with purposive sampling technique. Data were collected through interviews and medical record data. Data were analyzed using Chi-square statistical analysis. We found that 61.7% of the patients were light smokers and 66.2% had immature senile cataracts, and the statistical analysis found a significant correlation between smoking level and senile cataract stadium (p=0.000. We concluded that there is a correlation between smoking level and senile cataract severity. Keywords: cataract; senile cataract severity; smoking level